Self Writing and World Mapping in Tim Bowling’s ’Downriver Drift’ (2000) and ’The Paperboy’s Winter’ (2003) - Martínez Serrano, Leonor María (Complutense Journal of English Studies, 2020)
Widely acclaimed as one of the best living Canadian authors, Tim Bowling has cultivated several literary genres with great talent and verbal craftsmanship. He has published twelve poetry collections to date, two works of creative non-fiction, and five novels, including Downriver Drift (2000), The Paperboy’s Winter (2003), The Bone Sharps (2007), The Tinsmith (2012) and The Heavy Bear (2017). This article explores the epistemological power of Bowling’s fiction as a mode of knowing the self and the nonhuman environment. More specifically, bearing in mind fundamental ecocritical tenets, it analyses how his two earliest novels, Downriver Drift and The Paperboy’s Winter, evoke notions of dwelling and a compelling sense of place, as the natural environment in them is much more than mere backdrop to the narratives unfolding in their respective plots. Written in elegantly wrought language rich in poetic resonance, Bowling’s novels remind their readership that fiction is a powerful tool to investigate the human condition and our surrounding world, where the human and the nonhuman coexist on democratic terms.